High-conductivity phosphor-copper alloy and surface treatment process thereof
By using sandblasting and pyrolysis annealing processes with composite coatings, the problem of easy corrosion of phosphor bronze alloys in humid environments was solved, achieving improved stability of high conductivity and enhanced wear and corrosion resistance, thus ensuring the reliability of rail transit traction motors.
Patent Information
- Application Number
- CN202511525335.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-24
- Publication Date
- 2025-11-21
- Estimated Expiration
- 2045-10-24
AI Technical Summary
In humid, saline rail transit environments, phosphor bronze alloys are prone to corrosion, forming a loose oxide film that can disrupt the electrical conductivity and, in severe cases, cause motor failure. Existing technologies cannot effectively solve the problems of easy wear and corrosion of phosphor bronze alloys.
After sandblasting, a composite coating is applied, followed by pyrolysis and annealing to form an intermediate layer. Then, an epoxy composite coating is applied. The composite coating, composed of phosphorus copper doped with molybdenum disulfide, copper powder, metal salts, and aniline trimer derivatives, enhances the interlayer bonding and corrosion resistance. Modified MXene improves the wear resistance and corrosion resistance of the epoxy coating.
It effectively prevents oxidation of phosphor bronze alloy surface, improves conductivity, enhances interlayer bonding, reduces the penetration of corrosive media, improves long-term corrosion resistance and wear resistance, and ensures conductivity continuity.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of phosphorus copper alloy surface treatment, in particular to a high-conductivity phosphorus copper alloy and a surface treatment process thereof. BACKGROUND
[0002] With the development of electrified trains towards high speed and heavy load, the operating conditions of traction motors as the core equipment of the power traction system are increasingly severe, and higher requirements are put forward for the material and performance of the equipment, which promotes the technological progress of high-end materials, especially high-performance copper alloy materials, and the breakthroughs in key technologies are emerging continuously. Therefore, the prospect of industrialization of the high-conductivity and easy-to-weld phosphorus copper alloy material series products for rail transit traction motors is very broad. The high-phosphorus copper alloy material is used to process the guide bar and the end ring, which solves the problem of the conductivity of the rotor guide bar. However, in the humid and salty rail transit environment, the copper surface is easily corroded to form a loose oxide film, and the falling off of the oxide film will cause the interruption of the conductive path, and even cause the motor to fail. Therefore, the phosphorus copper alloy still faces the key problems of insufficient surface performance such as easy wear and corrosion in the long-term service of the traction motor, and it is urgent to further strengthen the surface treatment technology. SUMMARY
[0003] The present application aims to provide a high-conductivity phosphorus copper alloy and a surface treatment process thereof to solve the problems in the prior art.
[0004] To achieve the above-mentioned purpose, the present application provides the following technical solutions: A surface treatment process of a high-conductivity phosphorus copper alloy, comprising the following process steps: after cleaning the phosphorus copper alloy, the surface is subjected to sand blasting treatment, then a composite coating is applied, the intermediate layer is obtained by pyrolysis and annealing, and then an epoxy composite coating is applied on the surface of the intermediate layer to form a surface layer; Preferably, the preparation steps of the composite coating comprise: S1: placing aniline and 4,4'-diamino diphenylamine sulfate in a hydrochloric acid solution, stirring and adding ammonium persulfate, stirring at 2-5 DEG C for 50-70 min, then filtering, washing and drying, adding p-xylylene glycol and anhydrous ethanol, passing nitrogen and reacting at 60-70 DEG C for 4-6 h, then filtering, washing and drying to obtain aniline trimer derivative, which is ready for use; S2: copper nitrate is mixed with sodium hydroxide, ethylenediamine, and hydrazine hydrate, heated to 55-60℃ for 4-5h, then centrifuged and dried to obtain copper powder; thiourea and ammonium molybdate tetrahydrate are placed in deionized water, stirred for 30-40min, then copper powder is added, and hydrothermal reaction is carried out at 180-200℃ for 20-24h, then calcined with sodium hypophosphite at 500-550℃ for 2h to obtain phosphorus-copper-doped molybdenum disulfide; the phosphorus-copper-doped molybdenum disulfide, copper powder, metal salt, and aniline trimer derivative are placed in N,N-dimethylformamide, and the composite coating is obtained by stirring and dispersing.
[0005] Preferably, the raw material components of the composite coating include, by mass fraction: 5-8 parts of phosphorus-copper-doped molybdenum disulfide, 1-3 parts of copper powder, 0.2-3 parts of metal salt, 20-30 parts of aniline trimer derivative, and 60-80 parts of N,N-dimethylformamide; Preferably, the raw material components of the aniline trimer derivative include, by mass fraction: 9-10 parts of aniline, 25-30 parts of 4,4'-diaminodiphenylamine sulfate, 10-20 parts of ammonium persulfate, and 5-10 parts of p-phenylenediformaldehyde; Preferably, the raw material components of the phosphorus-copper-doped molybdenum disulfide include, by mass fraction: 8-10 parts of thiourea, 4-5 parts of ammonium molybdate tetrahydrate, 1-1.5 parts of copper powder, and 80-100 parts of sodium hypophosphite; Preferably, the metal salt is one or a combination of nickel acetate, titanium acetate, chromium acetate, and lanthanum acetate; Preferably, the preparation steps of the epoxy composite coating are as follows: Step 1: aniline and 4,4'-diaminodiphenylamine sulfate are placed in a hydrochloric acid solution, stirred and dissolved, and ammonium persulfate solution is added dropwise, then stirred and reacted at 2-5℃ for 50-70min, filtered, washed, dried, then added with 5-fluorosalicylaldehyde and anhydrous ethanol, introduced with nitrogen, and reacted at 45-55℃ for 4-6h, then filtered, washed, and dried to obtain a fluorine-containing aniline trimer derivative for standby; Step 2: carbon titaniumized aluminum is mixed with lithium fluoride and hydrochloric acid, stirred for 24h, then washed to neutral, placed in a low-temperature alkali solution, ultrasonicated for 2-3h, then added with benzoic acid diazonium salt, stirred for 4-6h, then centrifuged, washed, and dried to obtain carboxylated MXene; the carboxylated MXene is placed in N,N-dimethylformamide and methanol solvents, added with fluorine-containing aniline trimer derivative, condensing agent, and catalyst, then heated to 60℃, stirred and reacted for 10-12h, then centrifuged, washed, and dried to obtain modified MXene; Step 3: the modified MXene and phosphorus-copper-doped molybdenum disulfide are dispersed in epoxy resin, added with a curing agent, stirred for 10min, then placed and degassed for standby.
[0006] Preferably, the raw material components of the fluorine-containing aniline trimer derivative include 9-10 parts of aniline, 25-30 parts of 4,4'-diamino diphenylamine sulfate, 10-20 parts of ammonium persulfate and 5-10 parts of 5-fluorosalicylaldehyde by mass fraction; Preferably, the raw material components of the modified MXene include 8-10 parts of carboxylated MXene, 2-5 parts of fluorine-containing aniline trimer derivative, 0.1-0.2 parts of condensing agent and 0.1-0.2 parts of catalyst by mass fraction; Preferably, the raw material components of the epoxy composite coating include 80-100 parts of epoxy resin, 1-3 parts of modified MXene, 1-3 parts of phosphorus copper doped molybdenum disulfide and 60-75 parts of curing agent by mass fraction; Preferably, the pyrolysis process step is to heat at 500-600℃ for 2h, then heat to 800-900℃ for 6-8h; the annealing process step is to heat at 200-300℃ for 1-2h; the curing temperature is 40-45℃, and the curing time is 20-24h; Preferably, the thickness of the intermediate layer is 10-50μm, and the thickness of the surface layer is 80-120μm; A high-conductivity phosphorus copper alloy is prepared by the above surface treatment process; Compared with the prior art, the application has the following beneficial effects: 1、The application is aimed at the surface treatment of a high-conductivity phosphorus copper alloy substrate to prevent the surface oxidation of the phosphorus copper alloy from causing a decrease in the conductivity; after sandblasting the surface of the substrate, a composite coating is applied, which is composed of phosphorus copper doped molybdenum disulfide, copper powder, metal salt and aniline trimer derivative; the doped phosphorus and copper in the molybdenum disulfide reduce the contact resistance between the coating layers caused by the difference in elements, avoid hindering the conductive transmission of the phosphorus copper alloy substrate, and on the other hand, the doped phosphorus can form Cu3P dispersed in the molybdenum disulfide or directly doped into the molybdenum disulfide to improve the hardness of the overall doped phase; after applying the composite coating, pyrolysis is carried out to realize the carbonization of the aniline trimer derivative in the coating, form microdiffusion between the phosphorus copper alloy substrate and the coating under high-temperature pyrolysis, improve the interlayer bonding force, and fill the gaps in the coating with the nitrogen-doped carbon caused by carbonization, while the doped elements such as nickel, titanium, chromium and lanthanum in the metal salt can refine the grains and enhance the bonding force between the intermediate layer and the phosphorus copper substrate; the doped molybdenum disulfide and copper powder form a dense coating to reduce the penetration of corrosive media; annealing after pyrolysis eliminates the pores and stress in the coating; 2. The application forms an intermediate layer on the surface of the phosphor copper alloy substrate with high conductivity, then coats the epoxy composite coating, further protects the intermediate layer, and improves the long-term corrosion resistance. Specifically, the selection of each component in the epoxy composite coating: first, the phosphor copper doped molybdenum disulfide in the intermediate layer cooperates with MXene to improve the conductivity and ensure the conductivity continuity between the substrate-intermediate layer-surface layer; second, the fluorine-containing aniline trimer derivative is obtained by oxidizing coupling of aniline and 4,4'-diamino diphenylamine sulfate to obtain aniline trimer, and then performing aminoaldehyde condensation with 5-fluorosalicylaldehyde to obtain a fluorine-containing aniline trimer derivative, which is grafted with carboxylated MXene to improve the dispersion uniformity of MXene and improve the compatibility with epoxy resin; by adding modified MXene and phosphor copper doped molybdenum disulfide to the epoxy resin, the wear resistance and long-term corrosion resistance of the epoxy surface layer are further enhanced. DETAILED DESCRIPTION
[0007] The technical solutions in the embodiments of the application will be described below clearly and completely. Obviously, the described embodiments are only part of the embodiments of the application, not all. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor belong to the protection scope of the application.
[0008] In the experiment, the preparation steps of carboxylated MXene are as follows: 5g carbon titanium aluminum is mixed with 6.25g lithium fluoride and 100mL hydrochloric acid with a concentration of 12mol / L for 24h, then washed to neutral, placed in a 5℃ sodium hydroxide solution with a concentration of 1mol / L, ultrasonic for 3h, then 10g benzoyl chloride is added, stirred for 6h, then centrifuged, washed and dried to obtain carboxylated MXene; wherein, the carbon titanium aluminum is purchased from Xin'anyan Technology, and the item number is 1012; The preparation steps of benzoyl chloride are as follows: 20mmol sodium hydroxide and 20mmol p-aminobenzoic acid are mixed in 500mL deionized water, stirred under ice bath conditions, and 25mmol sodium nitrite salt is added, the pH is adjusted to be acidic, and stirred for 1h to obtain benzoyl chloride; The preparation steps of copper powder are as follows: 50mL copper nitrate solution with a concentration of 0.1mol / L is mixed with 750mL sodium hydroxide with a concentration of 20mol / L, 5mL ethylenediamine and 0.8mL hydrazine hydrate are added, heated to 60℃ for 4h, then centrifuged and dried to obtain copper powder; The epoxy resin type is E51, and the curing agent type is D230, both purchased from Jinan Qingtian Chemical Technology Co., Ltd.; The chemical composition of the phosphor copper alloy includes 0.0026%P, 0.0010%Zn, 99.97%Cu+Ag and the rest of the inevitable impurity elements by mass percentage.
[0009] Embodiment 1: The present embodiment provides a surface treatment process of high-conductivity phosphor copper alloy, comprising the following process steps: Step 1: 4.66 g of aniline and 14.88 g of 4,4'-diaminodiphenylamine sulfate are placed in a 500 mL 1 mol / L hydrochloric acid solution, and a 100 mL hydrochloric acid solution containing 10 g of ammonium persulfate is added dropwise. After stirring and reacting at 5°C for 1 h, the mixture is filtered and washed, dried, mixed with 3 g of p-phenylenediamine, and then placed in 100 mL of anhydrous ethanol. Nitrogen is introduced and the mixture is heated at 70°C for 6 h. After filtration and washing, the mixture is dried to obtain aniline trimer derivative for later use. 3.82 g of thiourea and 1.88 g of ammonium molybdate tetrahydrate are placed in deionized water and stirred for 30 min. Then, 0.40 g of copper powder is added, and the mixture is hydrothermally reacted at 200°C for 20 h. Then, 40 g of sodium hypophosphite is added and calcined at 500°C for 2 h to obtain phosphor copper-doped molybdenum disulfide. The phosphor copper-doped molybdenum disulfide, copper powder, chromium acetate, and aniline trimer derivative are placed in N,N-dimethylformamide and stirred to obtain a composite coating; Step 2: 4.67 g of aniline and 14.87 g of 4,4'-diaminodiphenylamine sulfate are placed in a 500 mL hydrochloric acid solution, and a 100 mL hydrochloric acid solution containing 10 g of ammonium persulfate is added dropwise. After stirring and reacting at 5°C for 1 h, the mixture is filtered and washed, dried, mixed with 3 g of 5-fluorosalicylaldehyde, and then placed in 100 mL of anhydrous ethanol. Nitrogen is introduced and the mixture is heated at 50°C for 6 h. After filtration and washing, the mixture is dried to obtain a fluorine-containing aniline trimer derivative for later use. 5 g of carboxylated MXene is placed in 90 mL of N,N-dimethylformamide and 10 mL of methanol solvent. Then, 1 g of fluorine-containing aniline trimer derivative, 0.1 g of carbodiimide, and 0.1 g of 4-dimethylaminopyridine are added, and the mixture is heated to 60°C and stirred for 10 h. After centrifugation, washing, and drying, modified MXene is obtained. The modified MXene and phosphor copper-doped molybdenum disulfide are dispersed in an epoxy resin, and a curing agent is added and stirred for 10 min. After standing and degassing, an epoxy composite coating is obtained. Step 3: The phosphor copper alloy is cleaned with anhydrous ethanol, sandblasted with brown corundum, coated with the composite coating, heated at 500°C for 2 h, then heated to 900°C for 6 h for pyrolysis, and then heated to 200°C for 2 h for annealing to obtain an intermediate layer with a thickness of 50 μm. The epoxy composite coating is coated on the surface of the intermediate layer, and the coating is cured at 40°C for 20 h to form a surface layer with a thickness of 100 μm. The composite coating includes 5 parts of phosphor copper-doped molybdenum disulfide, 2 parts of copper powder, 1 part of chromium acetate, 20 parts of aniline trimer derivative, and 80 parts of N,N-dimethylformamide, by mass. The epoxy coating includes 100 parts of epoxy resin, 1 part of modified MXene, 1 part of phosphor copper-doped molybdenum disulfide, and 60 parts of a curing agent.
[0010] Example 2: This example provides a surface treatment process for a high-conductivity phosphor bronze alloy, including the following process steps: Step 1: 4.66 g of aniline and 14.87 g of 4,4'-diaminodiphenylamine sulfate were placed in 500 mL of hydrochloric acid solution and stirred to dissolve. 100 mL of hydrochloric acid solution containing 10 g of ammonium persulfate was added dropwise. The mixture was stirred at 5 °C for 1 h, then filtered, washed, and dried. The resulting product was mixed with 3 g of terephthalaldehyde and placed in 100 mL of anhydrous ethanol. Nitrogen gas was introduced, and the mixture was kept at 70 °C for 6 h. The solid was then extracted and dried to obtain the aniline trimer derivative for later use. 3.82g of thiourea and 1.87g of ammonium molybdate tetrahydrate were placed in deionized water and stirred for 30 min. Then, 0.50g of copper powder was added and the mixture was hydrothermally reacted at 200℃ for 20 h. After that, it was calcined with 40g of sodium hypophosphite at 500℃ for 2 h to obtain copper-doped molybdenum disulfide. Copper-doped molybdenum disulfide, copper powder, nickel acetate, chromium acetate, lanthanum acetate and aniline trimer derivative were placed in N,N-dimethylformamide and stirred to disperse to obtain a composite coating. Step 2: 4.66 g of aniline and 14.85 g of 4,4'-diaminodiphenylamine sulfate were placed in 500 mL of hydrochloric acid solution, stirred and dissolved, and 100 mL of hydrochloric acid solution containing 10 g of ammonium persulfate was added dropwise. The mixture was stirred at 5 °C for 1 h, filtered, washed, dried, and then mixed with 3 g of 5-fluorosalicylaldehyde in 100 mL of anhydrous ethanol. Nitrogen gas was introduced and the mixture was kept at 50 °C for 6 h. The solid was extracted and dried to obtain the fluoroaniline trimer derivative for later use; 5 g of carboxyl group MXene was placed in 90 mL of N,N-dimethylformamide and 10 mL of methanol solvent, and 1.5 g of fluoroaniline trimer derivative, 0.1 g of carbodiimide and 0.1 g of 4-dimethylaminopyridine were added. The mixture was heated to 60 °C and stirred for 10 h. After centrifugation, washing and drying, modified MXene was obtained. Modified MXene and copper phosphate doped molybdenum disulfide were dispersed in epoxy resin, and a curing agent was added and stirred for 10 min. After standing to degas, an epoxy composite coating was obtained. Step 3: After cleaning the phosphor bronze alloy with anhydrous ethanol, it is sandblasted with brown corundum, then coated with a composite coating. After holding at 550℃ for 2 hours, the temperature is raised to 900℃ and held for 6 hours for pyrolysis, and then annealed at 300℃ for 2 hours to obtain an intermediate layer with a thickness of 50μm. An epoxy composite coating is then coated on the surface of the intermediate layer and cured at 40℃ for 20 hours to form a surface layer with a thickness of 100μm. The composite coating, by weight, comprises: 6 parts of copper-doped molybdenum disulfide, 1 part of copper powder, 1 part of nickel acetate, 1 part of chromium acetate, 1 part of lanthanum acetate, 20 parts of aniline trimer derivative and 80 parts of N,N-dimethylformamide. The epoxy coating comprises: 100 parts epoxy resin, 2 parts modified MXene, 2 parts phosphorus copper doped molybdenum disulfide and 60 parts curing agent.
[0011] Embodiment 3: The present embodiment provides a surface treatment process of high-conductivity phosphor copper alloy, comprising the following process steps: Step 1: 4.66 g of aniline and 14.88 g of 4,4'-diamino diphenylamine sulfate are placed in a 500 mL hydrochloric acid solution, and a 100 mL hydrochloric acid solution containing 10 g of ammonium persulfate is added dropwise. After stirring and reacting at 5°C for 1 h, the mixture is filtered, washed, and dried. Then, 3 g of p-phenylenediamine is mixed with 100 mL of anhydrous ethanol, and nitrogen is introduced. After reacting at 70°C for 6 h, the solid is extracted, dried, and used as an aniline trimer derivative. 3.82 g of thiourea and 1.87 g of ammonium molybdate tetrahydrate are placed in deionized water, stirred for 30 min, and then 0.60 g of copper powder is added. After hydrothermal reaction at 200°C for 20 h, the mixture is calcined with 40 g of sodium hypophosphite at 550°C for 2 h to obtain phosphor copper-doped molybdenum disulfide. The phosphor copper-doped molybdenum disulfide, copper powder, nickel acetate, chromium acetate, lanthanum acetate, and aniline trimer derivative are placed in N,N-dimethylformamide, and stirred and dispersed to obtain a composite coating; Step 2: 4.65 g of aniline and 14.88 g of 4,4'-diamino diphenylamine sulfate are placed in a 500 mL hydrochloric acid solution, and a 100 mL hydrochloric acid solution containing 10 g of ammonium persulfate is added dropwise. After stirring and reacting at 5°C for 1 h, the mixture is filtered, washed, and dried. Then, 3 g of 5-fluorosalicylaldehyde is mixed with 100 mL of anhydrous ethanol, and nitrogen is introduced. After reacting at 50°C for 6 h, the solid is extracted, dried, and used as a fluorine-containing aniline trimer derivative. 5 g of carboxylated MXene is placed in 90 mL of N,N-dimethylformamide and 10 mL of methanol solvent, and 2 g of fluorine-containing aniline trimer derivative, 0.1 g of carbodiimide, and 0.1 g of 4-dimethylaminopyridine are added. After stirring and reacting at 60°C for 10 h, the mixture is centrifuged, washed, and dried to obtain modified MXene. The modified MXene and phosphor copper-doped molybdenum disulfide are dispersed in epoxy resin, and a curing agent is added and stirred for 10 min. After standing and degassing, an epoxy composite coating is obtained. Step 3: The phosphor copper alloy is cleaned with anhydrous ethanol, sandblasted with brown corundum, coated with the composite coating, and then pyrolyzed at 600°C for 2 h, 900°C for 8 h, and 300°C for 2 h to obtain an intermediate layer with a thickness of 50 μm. The epoxy composite coating is coated on the surface of the intermediate layer, and cured at 40°C for 20 h to form a surface layer with a thickness of 100 μm. The composite coating includes 8 parts of phosphor copper-doped molybdenum disulfide, 2 parts of copper powder, 1 part of nickel acetate, 1 part of chromium acetate, 1 part of lanthanum acetate, 20 parts of aniline trimer derivative, and 80 parts of N,N-dimethylformamide, by mass. The epoxy coating includes 100 parts of epoxy resin, 3 parts of modified MXene, 2 parts of phosphor copper-doped molybdenum disulfide, and 60 parts of a curing agent.
[0012] Comparative Example 1: As a control experiment of Example 3, different from it is that: no metal salt is added in the composite coating; the specific steps are as follows: Step 1: 4.66 g of aniline and 14.88 g of 4,4'-diaminodiphenylamine sulfate are placed in 500 mL of hydrochloric acid solution, stirred and dissolved, 100 mL of hydrochloric acid solution containing 10 g of ammonium persulfate is added dropwise, stirred at 5°C for 1 h, then filtered and washed, dried, mixed with 3 g of p-phenylenediamine, and placed in 100 mL of anhydrous ethanol, nitrogen is introduced, and the reaction is carried out at 70°C for 6 h, then the solid is extracted, dried, and obtained as an aniline trimer derivative; 3.82 g of thiourea, 1.87 g of ammonium molybdate tetrahydrate are placed in deionized water, stirred for 30 min, 0.60 g of copper powder is added, hydrothermal reaction is carried out at 200°C for 20 h, then 40 g of sodium hypophosphite is calcined at 550°C for 2 h to obtain phosphorus-copper-doped molybdenum disulfide; the phosphorus-copper-doped molybdenum disulfide, copper powder and aniline trimer derivative are placed in N,N-dimethylformamide, stirred and dispersed to obtain a composite coating; Step 2: 4.65 g of aniline and 14.88 g of 4,4'-diaminodiphenylamine sulfate are placed in 500 mL of hydrochloric acid solution, stirred and dissolved, 100 mL of hydrochloric acid solution containing 10 g of ammonium persulfate is added dropwise, stirred at 5°C for 1 h, then filtered and washed, dried, mixed with 3 g of 5-fluorosalicylaldehyde, and placed in 100 mL of anhydrous ethanol, nitrogen is introduced, and the reaction is carried out at 50°C for 6 h, then the solid is extracted, dried, and obtained as a fluorine-containing aniline trimer derivative; 5 g of carboxylated MXene is placed in 90 mL of N,N-dimethylformamide and 10 mL of methanol solvent, 2 g of fluorine-containing aniline trimer derivative, 0.1 g of carbodiimide and 0.1 g of 4-dimethylaminopyridine are added, and the reaction is carried out at 60°C for 10 h after stirring, then centrifuged, washed and dried to obtain modified MXene; the modified MXene and phosphorus-copper-doped molybdenum disulfide are dispersed in epoxy resin, 10 min after stirring, a curing agent is added, and the epoxy composite coating is obtained after standing and degassing; Step 3: The phosphorus-copper alloy is cleaned with anhydrous ethanol, sandblasted with brown corundum, then coated with the composite coating, pyrolyzed at 600°C for 2 h, then heated to 900°C for 8 h, and then annealed at 300°C for 2 h to obtain an intermediate layer with a thickness of 50 μm; the epoxy composite coating is coated on the surface of the intermediate layer, and the surface layer with a thickness of 100 μm is formed after curing at 40°C for 20 h; Among them, according to the mass fraction, the composite coating includes: 8 parts of phosphorus-copper-doped molybdenum disulfide, 2 parts of copper powder, 20 parts of aniline trimer derivative and 80 parts of N,N-dimethylformamide; The epoxy coating includes: 100 parts of epoxy resin, 3 parts of modified MXene, 2 parts of phosphorus-copper-doped molybdenum disulfide and 60 parts of curing agent.
[0013] Comparative Example 2: As a control experiment of Example 3, different from it is that: the phosphor copper doped molybdenum disulfide in the composite coating and the epoxy composite coating is replaced by molybdenum disulfide, and the specific steps are as follows: Step 1: 4.66 g of aniline and 14.88 g of 4,4'-diamino diphenylamine sulfate were placed in 500 mL of hydrochloric acid solution, and 100 mL of hydrochloric acid solution containing 10 g of ammonium persulfate was added dropwise. After stirring and dissolving at 5°C for 1 h, the mixture was filtered, washed and dried. Then, 3 g of p-phenylenediamine was mixed with 100 mL of anhydrous ethanol, and nitrogen was introduced. After reaction at 70°C for 6 h, the solid was extracted, dried, and mixed with 3 g of 5-fluorosalicylaldehyde to obtain a fluorine-containing aniline trimer derivative; 3.82 g of thiourea and 1.87 g of molybdenum ammonium sulfate tetrahydrate were placed in deionized water, stirred for 30 min, and then subjected to hydrothermal reaction at 200°C for 20 h. After calcination at 550°C for 2 h, molybdenum disulfide was obtained. The molybdenum disulfide, copper powder, nickel acetate, chromium acetate, lanthanum acetate, and the fluorine-containing aniline trimer derivative were placed in N,N-dimethylformamide, and stirred and dispersed to obtain a composite coating; Step 2: 4.65 g of aniline and 14.88 g of 4,4'-diamino diphenylamine sulfate were placed in 500 mL of hydrochloric acid solution, and 100 mL of hydrochloric acid solution containing 10 g of ammonium persulfate was added dropwise. After stirring and dissolving at 5°C for 1 h, the mixture was filtered, washed and dried. Then, 3 g of p-phenylenediamine was mixed with 100 mL of anhydrous ethanol, and nitrogen was introduced. After reaction at 70°C for 6 h, the solid was extracted, dried, and mixed with 3 g of 5-fluorosalicylaldehyde to obtain a fluorine-containing aniline trimer derivative; 3.82 g of thiourea and 1.87 g of molybdenum ammonium sulfate tetrahydrate were placed in deionized water, stirred for 30 min, and then subjected to hydrothermal reaction at 200°C for 20 h. After calcination at 550°C for 2 h, molybdenum disulfide was obtained. The molybdenum disulfide, copper powder, nickel acetate, chromium acetate, lanthanum acetate, and the fluorine-containing aniline trimer derivative were placed in N,N-dimethylformamide, and stirred and dispersed to obtain a composite coating; Step 3: The phosphor copper alloy was cleaned with anhydrous ethanol, sandblasted with brown corundum, coated with the composite coating, and then pyrolyzed at 600°C for 2 h, 900°C for 8 h, and 300°C for 2 h to obtain an intermediate layer with a thickness of 50 μm; the surface of the intermediate layer was coated with an epoxy composite coating, and the coating was cured at 40°C for 20 h to form a surface layer with a thickness of 100 μm; The composite coating includes 8 parts of molybdenum disulfide, 2 parts of copper powder, 1 part of nickel acetate, 1 part of chromium acetate, 1 part of lanthanum acetate, 20 parts of aniline trimer derivative, and 80 parts of N,N-dimethylformamide; The epoxy coating includes 100 parts of epoxy resin, 3 parts of modified MXene, 2 parts of molybdenum disulfide, and 60 parts of curing agent.
[0014] Comparative Example 3: As a control experiment of Example 3, different from it is that: the modified MXene is replaced by MXene, the specific steps are as follows: Step 1: 4.66 g of aniline and 14.88 g of 4,4'-diamino diphenylamine sulfate were placed in a 500 mL hydrochloric acid solution, and a 100 mL hydrochloric acid solution containing 10 g of ammonium persulfate was added dropwise. After stirring at 5℃ for 1 h, it was filtered and washed, dried, and mixed with 3 g of p-phenylenediamine. Then, it was placed in 100 mL of anhydrous ethanol, nitrogen was introduced, and it was reacted at 70℃ for 6 h. After extracting the solid, it was dried to obtain aniline trimer derivative for use; 3.82 g of thiourea, 1.87 g of ammonium molybdate tetrahydrate were placed in deionized water, stirred for 30 min, and then 0.60 g of copper powder was added. After hydrothermal reaction at 200℃ for 20 h, it was calcined with 40 g of sodium hypophosphite at 550℃ for 2 h to obtain phosphorus-copper-doped molybdenum disulfide; the phosphorus-copper-doped molybdenum disulfide, copper powder, nickel acetate, chromium acetate, lanthanum acetate, and aniline trimer derivative were placed in N,N-dimethylformamide, and stirred and dispersed to obtain a composite coating; Step 2: MXene and phosphorus-copper-doped molybdenum disulfide were dispersed in epoxy resin, and a curing agent was added and stirred for 10 min, then it was left to stand and degassed to obtain an epoxy composite coating; Step 3: The phosphorus-copper alloy was cleaned with anhydrous ethanol, then sandblasted with brown corundum, and then coated with the composite coating. After heat treatment at 600℃ for 2 h, it was heated to 900℃ for 8 h for pyrolysis, and then cooled to 300℃ for 2 h for annealing to obtain an intermediate layer with a thickness of 50 μm; an epoxy composite coating was coated on the surface of the intermediate layer, and cured at 40℃ for 20 h to form a surface layer with a thickness of 100 μm; Among them, according to the mass fraction, the composite coating includes: 8 parts of phosphorus-copper-doped molybdenum disulfide, 2 parts of copper powder, 1 part of nickel acetate, 1 part of chromium acetate, 1 part of lanthanum acetate, 20 parts of aniline trimer derivative, and 80 parts of N,N-dimethylformamide; The epoxy coating includes: 100 parts of epoxy resin, 3 parts of MXene, 2 parts of phosphorus-copper-doped molybdenum disulfide, and 60 parts of a curing agent.
[0015] Detection test: Adhesion test: The adhesion test was carried out according to GB / T9286-2021 "Paints and varnishes: Cross-cut test", the temperature was 25℃, the relative humidity was 50%, the cutting interval was 3 mm, the cutting edge was completely smooth, and the falling off was 0 level standard, the cutting edge had a little falling off, but the affected cross-cut area was not more than 5% as 1 level standard, and the cutting edge had falling off and the affected cross-cut area was more than 5% but not more than 15% as 2 level standard; Friction and wear performance test: the surface treated phosphor copper alloy prepared in examples 1-3 and comparative examples 1-3 was taken, a multifunctional surface tester was used, a 6mm GCr bearing steel ball was used as the counter abrasive material, a load of 20N was applied, the reciprocating speed was 100mm / min, the test was carried out for 30min, and the volume wear rate data was recorded in table 1; Long-term corrosion resistance test: according to GB / T 10125-2021 neutral salt spray test, 3% sodium chloride neutral solution was used, the temperature was 35℃, after 1600h test, the surface of the sample was observed, the sample with complete surface without damage was recorded as qualified sample, the rest was recorded as unqualified, and recorded in table 1; Table 1
[0016] Conclusion: from the above data, it can be seen that the surface treatment process of example 3 is better than that of examples 1 and 2, and excellent interlayer bonding, wear resistance and long-term corrosion resistance are obtained; while comparative example 1 does not add metal salt in the composite coating, which has a slight effect on the test performance; in comparative example 2, the phosphor copper doped with molybdenum disulfide in the composite coating and the epoxy composite coating is replaced by molybdenum disulfide, which has a great influence on the test performance; in comparative example 3, only the modified MXene on the surface is replaced by conventional MXene, the compatibility between the filler and the resin decreases and the fluorine-containing Schiff base grafting is lacking, and the wear resistance and corrosion resistance decrease obviously.
[0017] It is apparent for those skilled in the art that the present application is not limited to the details of the above exemplary embodiments, but can be implemented in other concrete forms without departing from the spirit or essential characteristics of the present application. Therefore, the embodiments should be considered in all aspects as illustrative and not restrictive, and the scope of the present application is defined by the appended claims rather than the above description, and it is intended to encompass all changes falling within the meaning and scope of the equivalent elements of the claims.
Claims
1. A surface treatment process for high-conductivity phosphor copper alloys, characterized in that, The process comprises the following steps: sand blasting the surface of the phosphor copper alloy after cleaning, then coating the composite coating, pyrolyzing and annealing to obtain an intermediate layer, then coating an epoxy composite coating on the surface of the intermediate layer, and solidifying to form a surface layer. The preparation steps of the composite coating comprise: S1: placing aniline and 4,4'-diamino diphenylamine sulfate in a hydrochloric acid solution, stirring and adding ammonium persulfate, stirring at 2-5 DEG C for 50-70 min, then filtering, washing and drying, adding p-xylylene glycol and anhydrous ethanol, passing nitrogen and reacting at 60-70 DEG C for 4-6 h, then filtering, washing and drying to obtain aniline trimer derivative, which is used as needed; S2: mixing copper nitrate, sodium hydroxide, ethylenediamine and hydrazine hydrate, heating to 55-60 DEG C for 4-5 h, then centrifuging and drying to obtain copper powder; placing thiourea and molybdenum ammonium sulfate tetrahydrate in deionized water, stirring for 30-40 min, then adding copper powder, hydrothermal reaction at 180-200 DEG C for 20-24 h, then calcining with sodium hypophosphite at 500-550 DEG C for 2 h to obtain phosphor copper doped molybdenum disulfide; placing phosphor copper doped molybdenum disulfide, copper powder, metal salt and aniline trimer derivative in N,N-dimethylformamide, stirring and dispersing to obtain a composite coating.
2. The process for surface treatment of high conductive phosphorous copper alloy as claimed in claim 1 wherein, The raw material components of the composite coating comprise, by mass fraction: 5-8 parts of phosphor copper doped molybdenum disulfide, 1-3 parts of copper powder, 0.2-3 parts of metal salt, 20-30 parts of aniline trimer derivative and 60-80 parts of N,N-dimethylformamide; the raw material components of the aniline trimer derivative comprise, by mass fraction: 9-10 parts of aniline, 25-30 parts of 4,4'-diamino diphenylamine sulfate, 10-20 parts of ammonium persulfate and 5-10 parts of p-xylylene glycol.
3. The process for surface treatment of high conductive phosphorous copper alloy as claimed in claim 1 wherein, The raw material components of the phosphor copper doped molybdenum disulfide comprise, by mass fraction: 8-10 parts of thiourea, 4-5 parts of molybdenum ammonium sulfate tetrahydrate, 1-1.5 parts of copper powder and 80-100 parts of sodium hypophosphite; the metal salt is one or more combinations of nickel acetate, titanium acetate, chromium acetate and lanthanum acetate.
4. The process for surface treatment of high conductive phosphorous copper alloy as claimed in claim 1 wherein, The preparation steps of the epoxy composite coating are: Step 1: placing aniline and 4,4'-diamino diphenylamine sulfate in a hydrochloric acid solution, stirring and dissolving, then adding an ammonium persulfate solution, stirring at 2-5 DEG C for 50-70 min, then filtering, washing and drying, then adding 5-fluorosalicylaldehyde and anhydrous ethanol, passing nitrogen and reacting at 45-55 DEG C for 4-6 h, then filtering, washing and drying to obtain a fluorine-containing aniline trimer derivative, which is used as needed; Step 2: mixing carbon titanium aluminum, lithium fluoride and hydrochloric acid, stirring for 24 h, then washing to neutral, placing in a low-temperature alkali solution, ultrasonicating for 2-3 h, then adding benzoic acid diazonium salt, stirring for 4-6 h, then centrifuging, washing and drying to obtain carboxylated MXene; placing the carboxylated MXene in N,N-dimethylformamide and methanol solvents, adding the fluorine-containing aniline trimer derivative, a condensing agent and a catalyst, then stirring at 60 DEG C for 10-12 h, then centrifuging, washing and drying to obtain modified MXene; Step 3: dispersing the modified MXene and the phosphor copper doped molybdenum disulfide in epoxy resin, then adding a curing agent, stirring for 10 min, then standing and defoaming for standby use.
5. The process for surface treatment of high conductive phosphorous copper alloy as claimed in claim 4 wherein, The raw material components of the fluorine-containing aniline trimer derivative include 9-10 parts of aniline, 25-30 parts of 4,4'-diamino diphenylamine sulfate, 10-20 parts of ammonium persulfate and 5-10 parts of 5-fluorosalicylaldehyde; the raw material components of the modified MXene include 8-10 parts of carboxylated MXene, 2-5 parts of the fluorine-containing aniline trimer derivative, 0.1-0.2 parts of a condensation agent and 0.1-0.2 parts of a catalyst.
6. The process for surface treatment of high conductive phosphorous copper alloy as claimed in claim 4 wherein, The raw material components of the epoxy composite coating include 80-100 parts of an epoxy resin, 1-3 parts of the modified MXene, 1-3 parts of phosphorus-copper-doped molybdenum disulfide and 60-75 parts of a curing agent.
7. The process for surface treatment of high conductive phosphorous copper alloy as claimed in claim 1 wherein, The process steps of pyrolysis are: holding at 500-600 DEG C for 2 hours, then heating to 800-900 DEG C and holding for 6-8 hours; the process steps of annealing are: holding at 200-300 DEG C for 1-2 hours; the curing temperature is 40-45 DEG C, and the curing time is 20-24 hours.
8. The process for surface treatment of high conductive phosphorous copper alloy as claimed in claim 1 wherein, The thickness of the intermediate layer is 10-50 microns; the thickness of the surface layer is 80-120 microns.
9. A high-conductivity phosphorous copper alloy characterized by, Prepared by the surface treatment process of claims 1-8. Prepared by the surface treatment process of claims 1-8.
Citation Information
Patent Citations
Preparation method of electrocatalyst based on copper-doped dicobalt phosphide
CN109841855A
Processing technology of antibacterial austenitic stainless steel band
CN115368760A
High-conductivity phosphorus-copper alloy material and preparation method thereof
CN116463518A
Cited By
High-strength and high-toughness brass material and preparation method thereof
CN121537872A